ANALYSIS OF A GOOD GOVERNANCE-BASED PUBLIC COMPLAINT SYSTEM: A NORMATIVE-EMPIRICAL APPROACH TO REALIZE INCLUSIVE AND ACCOUNTABLE JUDICIAL SERVICES - Khaerulnisa; Ali Rahman (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
Public service in the judicial sector is a key indicator of state accountability as well as a reflection of public trust in legal institutions. However, the complaint system at the Makassar District Court still faces various normative and structural obstacles that hinder the realization of good governance principles. This study aims to analyze the effectiveness of the public complaint system within the judiciary and to identify the barriers that emerge in its implementation. The research employs a normative-empirical approach, combining legal analysis of public service regulations with field observations through interviews, documentation, and case studies. The findings reveal that although several digital innovations have been introduced, such as e-Court, SIPP, and e-Berpadu, the complaint system has not yet fully ensured transparency, accountability, and equal access for all justice seekers. The main challenges include regulatory harmonization, limited human resource capacity, cultural resistance, inadequate infrastructure, and fragmented complaint channels that lack integration. These results highlight the need for a policy model that integrates top-down regulations with bottom-up community participation, in order to create an inclusive, transparent, and accountable complaint mechanism in line with the principles of good governance.